Chatbots as Online Chat Conversation in the Education Sector - Tira Nur Fitria; Nurmala Elmin Simbolon; Afdaleni Afdaleni (Institut Teknologi Bisnis AAS Indonesia, 2023)
Chatbot technologies as virtual assistants have significantly emphasized streamlining and augmenting learning processes by integrating pedagogical approaches and innovative technologies. This research reviews the use of chatbots in education. The results of this review provide a comprehensive comprehension of the prior research on the use of Chatbots in education, including information on existing studies and its benefits, as well as prospective research areas on implementing Chatbot technology in the education sector. This study utilizes library research. The analysis shows that Artificial Intelligence technology permits incorporating Chatbot systems into various educational contexts and purposes, including for teachers, students, and administrators (institutional employees). First, teachers using chatbots can be virtual assistants for teachers to save time, including setting schedules, answering questions from students, and providing technical information about the learning system. Thus, the teacher has much time to prepare lesson plans or subject matter, make a set of questions, check assignments, and make other teaching preparations. Second, students using a chatbot can analyze student needs and provide teaching materials that are appropriate and specific to their needs. Learning can be done anytime and anywhere because of its ability to be able to reply to chats automatically. Chatbots will make it easier for students to get material and ask questions if they experience difficulties. Chatbots also make teaching and learning more manageable and teach-student communication and activities. Third, administrators using chatbots can simplify administration. The staff would be assisted in conveying information related to administrative matters and the student's registration process. Chatbots can be one of the best solutions to serve users by answering simple questions anytime without stopping. Chatbots can send broadcast messages to all students at once, and the data provided will be more personal, such as a reminder of tuition payments. Day by day, the popularity of chatbots is getting more attention and has penetrated the education sector. Chatbots should not threaten humans, but t can be used to help them. The teacher's role may be one of the parties that can be replaced by AI technology. However, it should be noted that AI cannot develop the character of both students and students, including providing motivation and establishing emotional relationships between teachers and students.